MEDIA PEMBELAJARAN INTERAKTIF DALAM PENERAPAN BLENDED LEARNING SELAMA TATAP MUKA TERBATAS DI SEKOLAH DASAR - Holy Ichda Wahyuni; Yustrisya Nih’matus Sa’diah; Nisa’ Aqidatul Fithri; Andas Nidaa’an Khofiyya; Diana Hanafiah (Universitas Muhammadiyah Surabaya, 2022)
Covid-19 has a broad impact on educational institutions, this outbreak brings various real challenges in various aspects, one of which is in the world of education. On the other hand, if viewed from the positive side, this outbreak can provide a unique opportunity to test students' preferences in situations where those who initially did face-to-face learning were replaced with blended learning systems. Blended learning is currently being discussed because the learning process in the classroom tends to be boring and the development of technology is increasingly widespread. Blended learning is a learning implementation system that combines the advantages of e-learning, the advantages of face-to-face, and practice. This learning integrates technology and online learning materials with conventional face-to-face classroom activities. However, in its implementation, blended learning still requires the application of interactive learning media so that learning objectives can be achieved optimally. This study aims to determine; (1) knowing the relevance of applying blended learning during limited face-to-face meetings in elementary schools; (2) to determine the application of interactive learning media used with blended learning-based learning systems. The method used in this study is a qualitative description method using the type of literature study research, namely by collecting literature data, reading and taking notes and processing research materials. The literature collected is literature that meets the inclusion criteria, which contains elements of keywords in blended learning, interactive media, and elementary school.Â Keywords: Blended learning, interactive media, elementary schoolÂ